Potential of histone deacetylase inhibitors for the therapy of ovarian cancer - Guo, Fengyi; Wang, Hongjing (Frontiers in Oncology, 2022)
Malignant ovarian tumors bear the highest mortality rate among all gynecological cancers. Both late tumor diagnosis and tolerance to available chemotherapy increase patient mortality. Accumulating evidence demonstrates that histone modifications play a key role in cancerization and progression. Histone deacetylases is associated with chromatin condensed structure and transcriptional repression and play a role in chromatin remodeling and epigenetics. Histone deacetylases are promising targets for therapeutic interventions intended to reverse aberrant epigenetic associated with cancer. Therefore, histone deacetylases inhibitors could be used as anti-cancer drugs. Preclinical studies have shown promising outcomes of histone deacetylases inhibitors in ovarian cancer while clinical trials have had mixed results and limited success as monotherapy. Therefore, combination therapy with different anticancer drugs for synergistic effects and newly selective histone deacetylases inhibitors development for lower toxicity are hot issues now. In this review, we summarize the latest studies on the classification and mechanisms of action of histone deacetylase and the clinical application of their inhibitors as monotherapy or combination therapy in ovarian cancer.